CONSTRUCTION OF A DOUBLE RING INFILTROMETER AND ITS USE FOR FIELD EVALUATION OF INFILTRATION CHARACTERISTICS OF TWO WOODLOT COMPARTMENTS OF AFAKA, KADUNA, NIGERIA - Onwuegbunam, Donatus; Onwuegbunam, N. E.; Bankole, H. F. (FUDMA JOURNAL OF SCIENCES, 2023)
A double ring infiltrometer of standard dimensions conforming to American Society for Testing and Materials (ASTM) specification was constructed and used for the evaluation of infiltration capacities of soil within two woodlot compartments of the Trial Afforestation Research Station (TARS), Afaka, Kaduna, Nigeria. The infiltration results will be necessary data tools in the use of woodlots as soil and water conservation measures. The construction was cost-effective and saved about 308 USD per infiltrometer when compared with the cost of importing a unit of the equipment. The basic infiltration capacities for the Eucalyptus and Cassia woodlots of sandy loam texture were found to be 231.4mm/hr and 195.8 mm/hr, respectively, after six hours. These values are about 10 to 15 times that for sandy loam (20 mm/hr to 30 mm/hr) on bare or arable soil of same texture. The infiltration characteristics were evaluated using four infiltration models – Horton, Kostiakov, Modified Kostiakov and Philip’s models. The Modified Kostiakov’s model gave the best prediction for the cumulative infiltration under Eucalyptus woodlot, while Kostiakov’s model gave the best prediction under Cassia woodlot. There were no significant differences in the performance of the models among themselves in each of the woodlots, and between the woodlots. It is recommended that the study be carried out in more compartments of the woodlot under different tree species to ascertain if there are variations in infiltration parameters, probably due to tree root types and bio-deterioration potential of the litters. There is need